CHALLENGES OF INCLUSIVE STUDENTS IN PARTICIPATING IN ENGLISH LEARNING AT SD ALAM MAHIRA BENGKULU - Mela Ayu Saputri; Ivan Achmad Nurcholis (Penerbit Lafadz Jaya, 2022)
This study aims to find out what challenges are experienced by inclusive children at SD Alam Mahira Bengkulu. Children with special needs are children with special characteristics that are different from children in general who always show mental, emotional, or physical retardation. Blind, deaf, learning difficulties, behavior disorders, and children with health problems who are included in Children with special needs or children with special needs. According to the 1945 Constitution article 31 paragraph 1 which reads: that all Indonesian citizens have the right to receive it, that is clear from the law. Quality education today, regardless of this aspect. This is because. The government is obliged to provide good education. No exception for children with special needs. Challenges are things or objects that upload a determination to improve the ability to solve problems. Exemplified as a stimulus to work harder and so on. Challenges are things or objects that need to be addressed. According to Fatimah Djajasudarma in Linguistic Method of Research and Study Methods (1993) text can be in the form of utterances, paragraphs, or discourses. Meanwhile, in the Big Indonesian Dictionary, challenge comes from a basic word which means a thing or object that needs to be overcome. Attitudes to the Challenges of Inclusive Education The development of teacher skills and teaching models is needed to support inclusive education. Inclusive education training for teachers is also a factor that can influence attitudes towards inclusive education.